Vernacular animalities: reading multispecies ethics in Hasan Azizul Haque's short stories - Ray, Sreyashi (Interventions (London, England), 2024)
This essay foregrounds new vernacular aesthetics of multispecies ethics through close readings of two short stories - "Shokun" ("Vulture") and "Amrityu Ajibon" ("Till Death, Through Life") - by Bengali writer Hasan Azizul Haque (1939-2021). Postcolonial literary criticism has predominantly focused on Haque's incisive portrayal of the consequences of the Partition of India and Bangladesh Liberation War on affected minorities, but his depictions of other-than-human subjects and interspecies relationalities implicated in postcolonial power dynamics have not received the critical attention that they merit. This essay draws on the analytical frameworks offered by interdisciplinary animal studies to demonstrate the agential roles of animals in Haque's stories. Through literary speculations on animal alterities and entangled human-animal vulnerabilities, the short stories studied in this essay articulate the impact of feudal economic structures and inter-class hierarchies on landless peasants and debt-bonded labourers in post-Partition Bengal. They elaborate the mechanisms through which vernacular knowledges about human-animal coexistence, communication, and co-constitution provide textual corollaries for subaltern consciousness, resistance, and moral upliftment. I argue that the material and semiotic dimensions of literary animal figures in the stories produce unique narrative instances of recuperative animal agencies through sustained attention to the corporeal dynamics and affective logics of interspecies interactions. I also argue that while the material aspects of interspecies relationships are manifested through embodied affect, their symbolic aspects become conspicuous through the textual preeminence of metonymic animals over their metaphoric configurations. I show that through different textual iterations of transspecies relatedness stemming from (but not limited to) two kinds of physical contiguity - a vulture's peck and a snake's bite - Haque's short stories critique both uncritical consolidation and outright disavowal of interspecies difference.